Hubungan Antara Media Sosial dan Perilaku Altruistik pada Generasi Z - Judijanto, Loso; Tjahyafi, Indra; Sastraatmadja, Achmad Harristhana Mauldfi; Maqfirah, Poetri AL-Viany; Astafi, Riki (Westscience Press, 2024)
This study examines the relationship between social media and altruistic behavior among Generation Z through a systematic literature review of 25 Scopus-indexed articles. Social media platforms have emerged as significant tools for fostering prosocial behavior, providing avenues for awareness, engagement, and collective action. Findings indicate that social media plays a dual role in shaping altruism by enabling actions such as fundraising and volunteering while also posing challenges like slacktivism and compassion fatigue. Generation Z's digital fluency and emphasis on authenticity shape their approach to altruistic behavior, with preferences for digital activism and campaigns aligned with their values. This study highlights the need for designing authentic, transparent, and impactful digital campaigns to promote sustained altruism and calls for further exploration of the long-term effects of social media-driven altruism.